Presence of multilobular necrosis on liver biopsy identifies corticosteroid responsiveness in acute indeterminate hepatitis. (5th January 2022) - Lin, Su; Araujo, Catarina; Hall, Andrew; Kumar, Rahul; Phillips, Alexandra; Hassan, Mohsin; Engelmann, Cornelius; Quaglia, Alberto; Jalan, Rajiv
Abstract: Background and Aims: Treatment of patients with severe indeterminate hepatitis (IAH) is an unmet need. Corticosteroids are often used in the management of these patients but criteria for the selection of patients for this intervention are arbitrary. The aims of this study were to analyse the clinical and pathological features of patients with IAH to define predictors of corticosteroid responsiveness. Methods: This study included consecutive patients with acute indeterminate hepatitis admitted to a single hospital and underwent a liver biopsy. The clinical manifestation and histopathological features of steroid and non‐steroid groups were compared and their relationship with corticosteroids response was evaluated. Results: Forty‐eight patients were included, 24 (50%) recovered and the other half underwent liver transplantation or died within 3‐months. Of the 48 cases, 24 received corticosteroids (initial dose of 45 ± 12 mg prednisolone). Corticosteroids were initiated 2.7 ± 3.8 days after admission. Liver biopsy was performed 2‐days (median, IQR 1‐3) after admission. Fifteen (62.5%) patients receiving corticosteroids survived without transplantation compared with 9 (37.5%) that did not receive steroids ( P = .149). In those with multilobular necrosis, 50% reduction in the death/transplantation rate was observed after steroid treatment ( P = .018). In patients without multilobular necrosis and with or without perivenulitis, corticosteroids did not impact the outcome. Response to corticosteroids was independent of the MELD score. Conclusions: The presence of multilobular necrosis on liver biopsy helps identify a subgroup of IAH cases who may benefit from the administration of corticosteroids.